Tracking Global Wokeism - Botz-Bornstein, Thorsten, (Religious Studies, Theology and Philosophy E-Books Online, Collection 2025., 2025)
In this volume, nineteen authors ask: does wokeness exist in the non-Western world? And if yes, is it imported from America or can it also have its own vernacular roots? Wokeness has helped advance the cause of social justice in many domains. However, a cursory search on the internet can yield the impression that 'woke' is now predominantly used in a negative fashion. The present book approaches woke from unusual philosophical angles that do not adhere to either pro or counter positions but that try to transcend purely ideological perspectives. The book shifts the debate to an international or global level by asking whether Wokeism also exists in the non-Western world.